PEMBELAJARAN LITERASI DI LPTK UNDANA MENYONGSONG GENERASI EMAS INDONESIA - Nai, Firmina A. (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
Schelfhout et al. (2006) quoted by Mehrak (in Asean EFL Journal, p. 3) via www.asean-efl-journal.com>pta_oct_08 , said that: to produce good prospective teachers, LPTK needs to equip prospective teachers with